Alien marine species of Libya: first inventory and new records in El-Kouf National Park (Cyrenaica) and the neighbouring areas - BAZAIRI, H.; SGHAIER, Y.R.; BENAMER, I.; LANGAR, H.; PERGENT, G.; BOURAS, E.; VERLAQUE, M.; SOUSSI, J.B.; ZENETOS, A. (Mediterranean Marine Science, 2013)
The presence of marine alien species in El-Kouf National Park and the neighbouring areas was assessed using a compilation of available information and observations, a field survey conducted on October 2010 in the framework of the MedMPAnet project and results of further monitoring during June and September 2012. A total of 9 alien species were reported: the Rhodophyta Asparagopsis taxiformis (Delile) Trevisan de Saint-Léon, the Chlorophyta Caulerpa racemosa var. cylindracea (Sonder) Verlaque, Huisman & Boudouresque, the crab Percnon gibbesi (H. Milne-Edwards, 1853) and the fishes Fistularia commersonii Rüppell, 1838, Siganus luridus (Rüppell, 1829), Siganus rivulatus Forsskål, 1775, Pempheris vanicolensis Cuvier, 1831, Lagocephalus sceleratus (Gmelin, 1789) and Sphyraena flavicauda Rüppell, 1838. Several of them were until now unknown for the National Park. The list of alien marine species of Libya is updated and discussed. Until now 63 marine aliens species were recorded along the Libyan coasts. These include 3 Foraminifera, 3 Ochrophyta, 5 Rhodophyta, 5 Chlorophyta, 1 Magnoliophyta, 11 Arthropoda, 13 Mollusca, 1 Echinodermata and 21 Chordata. Among these Non Indigenous Species, 43 are known as established along the Libyan coast including 8 invasive, 11 casual, 6 questionable, 3 cryptogenic and 1 unknown. An in-depth study of the marine organisms would substantially increase the number of alien species occurring in Libya. Monitoring of marine assemblages of MPAs is a valuable opportunity to go further into the knowledge of native and introduced species.